Full-thickness skin reconstruction with basic fibroblast growth factor-impregnated collagen-gelatin sponge - Matsumine, Hajime (Regen Ther, 2019)
INTRODUCTION: This study examined the usefulness of basic fibroblast growth factor impregnated collagen-gelatin sponge (bFGF-CGS) in reconstructive surgery for various acute skin defects including deep dermal burns, facial full-thickness skin defects, and finger amputations as the first clinical application. METHODS: Reconstructive surgery was performed in two stages with bFGF-CGS in 8 male subjects, ranging in age from 6 to 84 years, with acute full-thickness skin defects. Following the adequate debridement of the defect, surgeons prepared a bFGF-CGS with bFGF solution at a dose of 7–14 mg/cm(2) approximately 10 min just before application and then secured the bFGF-CGS in place with non-absorbable sutures. Second-stage wound closure was performed with autologous skin grafting following adequate dermis-like tissue regeneration at the site postoperatively. Follow-up was continued for 6 months. RESULTS: Of the 8 subjects, the mean duration from the adequate vascularization of the dermis-like tissue until the second-stage autologous skin graft was 22 ± 4 days. Wound closure was achieved in all cases; the mean duration until wound closure was 32 ± 8 days. During the 6-month follow-up period, no wound infection, recurrent skin ulceration, and no exposure of tendon, bone, and cartilage were observed, and there were no cases of indirectly restricted range of motion from postoperative scar contracture and none with disfiguring scars. CONCLUSION: The authors achieved favorable outcomes following reconstructive surgery with a hybrid artificial dermis impregnated with bFGF for treating acute full-thickness skin defects. bFGF-CGS serves as a convenient regenerative device requiring no specialized medical facilities.